Emission characteristics and potential of macroparticle in beam-plasma discharge - Bizyukov, A.A.; Romaschenko, E.V.; Sereda, K.N.; Chibisov, A.D.; Nazarov, A.V. (Вопросы атомной науки и техники, 2008)
Dust plasma now is one of most intensively developing directions of modern plasma physics. We will focus on the main task of the physical processes appearing in gas-discharge plasma with dust particles is definition of the value of electric potential of macroparticles, despite of the significant number of articles devoted to this problem. In the present work the behaviour of floating electric potential of a particle in beam-plasma systems over the average energies of electron beams taking into account a secondary electron emission and also an auto-electron emission is studied. За теперішнього часу пилова плазма є одним з напрямків сучасної фізики плазми, які найбільш інтенсивно розвиваються. Незважаючи на велику кількість робіт, що присвячені цьому питанню, при вивченні фізичних процесів, що відбуваються у газорозрядній плазмі з пиловими частинками, актуальною проблемою є визначення величини електричного потенціалу макрочастинки. В даній роботі вивчається поведінка плаваючого електричного потенціалу макрочастинки у плазмово-пучкових системах у діапазоні середніх енергій електронних пучків з урахуванням вторинної електронної емісії та автоелектронної емісії. Пылевая плазма в настоящее время является одним из наиболее интенсивно развивающихся направлений современной физики плазмы. Несмотря на множество работ посвященных этому вопросу, при изучении физических процессов, происходящих в газоразрядной плазме с пылевыми частицами, актуальной задачей является определение величины электрического потенциала микрочастиц. В настоящей работе изучается поведение плавающего электрического потенциала макрочастицы в пучково-плазменных системах в диапазоне средних энергий электронных пучков с учетом вторичной электронной эмиссии, а также авто-электронной эмиссии.